The Shemale Pesantren of Mon-Thurs Yogyakarta: An Existential Medium of Expression for Transsexual Muslims: [Pesantren Waria Senin-Kamis Al-Fatah Yogyakarta: Sebuah Media Eksistensi Ekspresi Keberagamaan Waria] - Arif Nuh Safri (UIN Sunan Kalijaga Yogyakarta, 2014)
Religion certainly is present in every human being, because it is an natural tendency. The presence of God in every human being is a necessity. Nevertheless, religious expression and Godliness will always vary. The concept of religiosity and Godliness will differ between the chaplain, students, scholars, with criminals, thieves, pickpockets, prostitutes and transvestites. Each one is identical to the role and experience of its own. Therefore, awareness of the differences in the identification of religion and God, should make man more flexibility to appreciate other people's religiosity and Godliness, although others are emerging from marginal groups, or the offender is considered a sin, so that everyone is aware of and comfortable with undergoing road religion and the way the Lord each believed. Through this article, the author will present a descriptive pattern diversity ekspreif shemale Shemale on Mondays and Thursdays at Pesantren al-Fatah Yogyakarta. At least, the courage to hold these institutions, has become proof of the existence of transgender religious expression on the face of this earth, once negated that should not be considered pious people who claim to be religious and atheist.[Agama pasti hadir dalam diri setiap manusia, karena itu merupakan fitrah yang terbawa sejak lahir. Kehadiran Tuhan dalam diri setiap manusia adalah sebuah keniscayaan. Namun demikian, ekspresi keberagamaan dan kebertuhanan akan selalu berbeda-beda. Konsep keberagamaan dan kebertuhanan akan berbeda antara kiyai, santri, sarjana, dengan koruptor, pencuri, pencopet, pelacur dan waria. Masing-masing identik dengan peran dan pengalaman tersendiri. Oleh sebab itu, kesadaran akan perbedaan identifikasi agama dan Tuhan, seharusnya menjadikan manusia lebih leluasa untuk menghargai keberagamaan dan kebertuhanan orang lain, walaupun orang lain tersebut muncul dari kaum marginal, atau kaum yang dianggap pelaku dosa, sehingga setiap orang dengan sadar dan nyaman menjalani jalan agama dan jalan Tuhannya masing-masing yang diyakini. Melalui artikel ini, penulis akan memaparkan secara deskriptif pola ekspreif keberagamaan waria di Pesantren Waria Senin Kamis al-Fatah Yogyakarta. Setidaknya, keberanian mengadakan lembaga ini, sudah menjadi bukti eksistensi ekspresi keberagamaan waria di muka bumi ini, sekaligus menegasikan bahwa tidak harus orang yang dianggap saleh yang boleh beragama dan mengaku bertuhan.]